A concretização dos valores sociais do trabalho baseada na jurisprudência do TST: o discurso jurídico e sua relação com a prática social - Deizimar Mendonça Oliveira (2018)
This dissertation is divided into two parts. The first is based on Foucault's view of discourse as a constitutive of social life, associated with the critical perspective of Fairclough, which relates discourse and subjectivity as capable of shaping social practices, and focuses on legal praxis within the Tribunal Superior do Trabalho (higher labor court), in order to examine the realization of social values of work, as a constitutional principle - thus endowed with a deontic quality - since their linguistic management. It is also supported by the notions of analogy and digitality presented by Pino, to consider the always proportionate relation of the senses, the continuities and ruptures constant of the structuring and transformation of the discourse. Considering the subjects and the space-time in which they are situated, discourse analysis comprising the principle of social values of work sought to be referenced in fourdimensional extensions, correlating the object (1) with the dimensions of ethos, which is linked to the construction of images of oneself and of the other in the discourse; of the logos, associated with the demonstrative dimension of the argument; and pathos, which comprises aspects of emotion and its feelings as constitutive of argumentation; (2) the place and time in which the object is inserted and the subjects in the discourse; and (3) the place and time of discourse in society (social practice). Understanding that every norm is based in a linguistic content and therefore requires the mediation of an interpreter, it is possible to unravel in judicial decisions the extent to which this constitutional principle has translated itself into a factor of reality. The interaction between language and social practice is not dissociated from its historicity, so, in order to understand the historical development of sedimentation of the principle, it was necessary to establish temporal landmarks and delimit the regularities and dispersions in the discursive formations located in the judgments, in order to the concreteness of the social values of work as a positive principle in the constitution. The second part proposes a critique of the argumentative construction of the TST, based on the relation between law and language and considering the structure of norms and the relation between normativity and reality. Taking the linguistic turn as a framework, originated mainly in the formulations of Gadamer and Wittgenstein, and the understanding that language is not merely an instrument, but is constitutive of reality and constituted by it, its possible to know the facts that lead to the understanding that the human knowledge is shared and subjective, and that truth is contingent, insofar as propositions, as figurative representations, may or may not correspond to reality. By his perfect reading of the relation between law and language and the need to break with the separation between « be » and « ought to be », between law and reality, Friedrich Müller's structuring theory of law is presented as a path to the realization of social values of labor, as a constitutional norm. It is from this perspective that the criticism is made to the jurisprudence of the TST. The results demonstrate that the principle under study has not been managed in order to allow effective transparency and controllability of decisions.